2018
DOI: 10.14419/ijet.v7i4.11.20804
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Diabetic Retinopathy by Using Deep Learning Neural Network

Abstract: This project presents a method to detect diabetic retinopathy on the fundus images by using deep learning neural network. Alexnet Convolution Neural Network (CNN) has been used in the project to ease the process of neural learning. The data set used were retrieved from MESSIDOR database and it contains 1200 pieces of fundus images. The images were filtered based on the project needed.  There were 580 pieces of images types .tif has been used after filtered and those pictures were divided into 2, which is Exuda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The best-reported accuracy was 63.2% for the InceptionV3 architecture. Hazim et al [60] used 580 images from the Messidor dataset to test the transfer learning of AlexNet. They opted for a two-class classification, and they cropped the images to 227 × 227.…”
Section: Paper Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The best-reported accuracy was 63.2% for the InceptionV3 architecture. Hazim et al [60] used 580 images from the Messidor dataset to test the transfer learning of AlexNet. They opted for a two-class classification, and they cropped the images to 227 × 227.…”
Section: Paper Reviewmentioning
confidence: 99%
“…Many private datasets were used as well in studies [53,57,64,68,69]. Many researchers like Tsighe et al [65], Li et al [55], Mohammadian et al [56], Hazim et al [60], Lam et al [61], and Lam et al [62] considered a binary classification task due to the lack of a sufficient number of images for some of the classes. In particular, the lack of severe cases images plays an important role because there are too few images that are available for training the network.…”
Section: The Datasets Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…The replicate study showed that selecting the suitable normalization method is very critical and is hence supposed to be used in the original study. Hazim Johari et al [13] used Alexnet deep learning neural network on retinal images for DR detection by using availability public MESSIDOR database. They demonstrated that Alexnet layers is the perfect layer for deep learning.…”
Section: Related Workmentioning
confidence: 99%
“…GoogleNet CNN platform was used by the authors in [11] in order to detect the symptoms of diabetic macular edema (DME) utilizing the benchmark MESSIDOR and the other is the E-Ophtha datasets. AlexNet based architecture was presented by the authors in [12] using the MESSIDOR dataset for diagnostic information extraction of DR severities. A zoon-in-Net based DR diagnostic platform was built by Wang, et al [13] for retinopathy detection and severity grading.…”
Section: Introductionmentioning
confidence: 99%